Ransom Drysdale’s Motives in Harlan Thrombey’s Death in Knives Out (2019): A Maslowian Perspective - Dharayya Mutiara Rohali; Agnes Widyaningrum (Wanastra: Jurnal Bahasa dan Sastra, 2026)
Knives Out (2019) presents Ransom Drysdale as a complex character whose motives are shaped by family conflict and inheritance. This study aims to analyze Ransom Drysdale's motives in Harlan Thrombey's death using Maslow's Hierarchy of Needs through a context-oriented approach. This study employed a qualitative descriptive design. The primary data consisted of selected scenes, dialogues, and character interactions involving Ransom Drysdale, which were collected through repeated viewing and note-taking. The data were analyzed by classifying them based on Maslow's Hierarchy of Needs and interpreting them using a context-oriented approach. The findings indicate that Ransom's physiological and safety needs were generally fulfilled, while the inheritance decision challenged his sense of security, belonging, and especially his esteem. Rather than explaining his actions as the direct result of unmet psychological needs, this study suggests that Maslow's Hierarchy of Needs provides an interpretive framework for understanding Ransom's motives within the familial context of the film.